Intensive Debulking Chemotherapy Improves the Short-Term and Long-Term Efficacy of Anti-CD19-CAR-T in Refractory/Relapsed DLBCL With High Tumor Bulk - Lyu, Cuicui; Cui, Rui; Wang, Jia; Mou, Nan; Jiang, Yanyu; Li, Wei; Deng, Qi (Frontiers in Oncology, 2021)
Anti-CD19 chimeric antigen receptor T (CAR-T) therapy has achieved remarkable effects in refractory/relapsed (R/R) diffuse large B-cell lymphoma (DLBCL). However, when high tumor bulk occurs, patients tend to early progression after CAR-T therapy. Here, we investigated whether pretreatment with intensive debulking chemotherapy could improve the outcome of CAR-T in such patients. 57 patients with R/R DLBCL were enrolled, and 42 patients received anti-CD19-CAR-T therapy. Among which, 25 patients (the combined group) with high tumor bulk received debulking chemotherapy and anti-CD19-CAR-T therapy sequentially. Another 17 patients (the control group) without high tumor bulk received anti-CD19-CAR-T therapy only. According to the response to debulking chemotherapy, patients of the combined group were divided into the chemo-sensitive and chemo-refractory groups. Within 2 months, the objective response rate (ORR) was higher in the chemo-sensitive group than in the chemo-refractory group (P=0.031). Grade 1 – 3 cytokine release syndrome (CRS) was reported, and no difference was shown in CRS grade distribution between the chemo-sensitive and chemo-refractory groups (P=0.514). The chemo-sensitive group demonstrated longer overall survival (OS) than the chemo-refractory group (P=0.042). Of the chemo-sensitive group, the 1-year disease free survival (DFS) and OS rates were 52.6% and 57.9%, respectively. Besides, no significant differences were found in ORR, DFS and OS between the chemo-sensitive and control groups (ORR: P=0.593; DFS: P= 0.762; OS: P=0.531). In summary, effective debulking chemotherapy improved the short-term ORR and long-term OS of CAR-T therapy in R/R DLBCL with high tumor bulk, with outcomes comparable to those of R/R DLBCL without high tumor bulk.